2021
DOI: 10.1111/imj.15230
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer screening in Australia and New Zealand: the evidence and the challenge

Abstract: Lung cancer remains the commonest cause of cancer death in Australia and New Zealand. Targeted screening of individuals at highest risk of lung cancer aims to detect early stage disease, which may be amenable to potentially curative treatment. While current policy recommendations in Australia and New Zealand have acknowledged the efficacy of lung cancer screening in clinical trials, there has been no implementation of national programmes. With the recent release of findings from large international trials, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…[28][29][30][31] Manners et al emphasised the importance of equitable access to screening for all populations, especially indigenous populations and those living in remote areas. 13 McLeod et al found that a national low-dose computed tomography screening programme in New Zealand was likely to be costeffective and health gains per capita were greater for M aori. 12 We believe that a lung cancer screening programme aimed at M aori is the most effective way of improving lung cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] Manners et al emphasised the importance of equitable access to screening for all populations, especially indigenous populations and those living in remote areas. 13 McLeod et al found that a national low-dose computed tomography screening programme in New Zealand was likely to be costeffective and health gains per capita were greater for M aori. 12 We believe that a lung cancer screening programme aimed at M aori is the most effective way of improving lung cancer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Successful models of assessment and pilot trials have been underway internationally for several years and can serve as a baseline to inform the best implementation plan for screening in each jurisdiction. 25 - 29…”
Section: Implement Cost-effective Clinically Efficacious and Equitabl...mentioning
confidence: 99%
“…Successful models of assessment and pilot trials have been underway internationally for several years and can serve as a baseline to inform the best implementation plan for screening in each jurisdiction. [25][26][27][28][29] Ensure Diagnosis of Lung Cancer Within 30 days of Referral Various temporal targets for key time points within the cancer patient journey exist for different countries, but there has previously been a lack of international consensus on a universal 'best practice' target. Unwarranted delays in diagnosis can rapidly shift lung cancer patients from being potentially curative to being difficult to treat, highlighting the importance of timely diagnosis to improve the possibility of treatment with curative intent.…”
Section: Implement Cost-effective Clinically Efficacious and Equitabl...mentioning
confidence: 99%
“…The diagnosis and management of peripheral pulmonary lesions (PPL) is rapidly evolving. As pulmonologists, we face the increasing burden of assessing PPLs, initially with the increasing numbers of computerized tomography (CT) chest scans performed for other indications (including CT coronary angiography), and more recently with the advent of lung cancer screening programmes 1,2 . It is therefore important that we have an evidence‐based approach to the assessment and management of PPLs, and there are several excellent documents available to help guide our approach 3–5 .…”
mentioning
confidence: 99%
“…As pulmonologists, we face the increasing burden of assessing PPLs, initially with the increasing numbers of computerized tomography (CT) chest scans performed for other indications (including CT coronary angiography), and more recently with the advent of lung cancer screening programmes. 1,2 It is therefore important that we have an evidence-based approach to the assessment and management of PPLs, and there are several excellent documents available to help guide our approach. [3][4][5] We feel that the management of PPLs is best guided by a multidisciplinary approach as the involvement and interaction between interventional radiologists, cardiothoracic surgeons and interventional pulmonologists is vital.…”
mentioning
confidence: 99%